How has access to legal cannabis changed over time? An analysis of the cannabis retail market in Canada 2 years following the legalisation of recreational cannabis. (12th July 2021) - Myran, Daniel T.; Staykov, Emiliyan; Cantor, Nathan; Taljaard, Monica; Quach, Bradley I.; Hawken, Steven; Tanuseputro, Peter
Abstract: Introduction: This study describes the legal recreational cannabis market across Canada over the 2 years following legalisation. We compared changes in access to the legal cannabis retail market for all provinces and territories (jurisdictions) in Canada and explored differences between jurisdictions. Methods: We collected data for all legal cannabis stores in Canada over five time periods following legalisation in October 2018. We examined the following measures by jurisdiction and retail model (public vs. private operation): absolute and per capita store numbers, hours of operation and store access across neighbourhoods. Results: Two years following legalisation, there were a total of 1183 legal cannabis stores open across Canada (3.7 stores per 100 000 individuals aged 15+). There was wide variation between jurisdictions in access to retail stores, with the lowest stores per capita in Quebec and Ontario (0.6 and 1.6 per 100 000), and the highest in Alberta and Yukon (14.3 per 100 000 in both). Jurisdictions with private retail models had more stores (4.8 vs. 1.0 per 100 000), held greater median weekly hours (80 vs. 69) and experienced greater store growth over time compared to public models. After adjusting for confounders, there were 1.96 times (95% confidence intervals: 1.84, 2.09) more cannabis stores within 1000 m of the lowest‐ compared to the highest‐income quintile neighbourhoods. Discussion and Conclusions: While access to the recreational cannabis retail market has increased following legalisation, there is substantial variation in access between jurisdictions and evidence of concentration in lower‐income neighbourhoods. These differences may contribute to disparities in cannabis use and harms.